Identification of the Aldo-Keto Reductase Responsible for d-Galacturonic Acid Conversion to l-Galactonate in Saccharomyces cerevisiae - Dorthe Rippert (MDPI AG, 2021)
d-galacturonic acid (d-GalUA) is the main constituent of pectin, a complex polysaccharide abundant in several agro-industrial by-products such as sugar beet pulp or citrus peel. During several attempts to valorise d-GalUA by engineering the popular cell factory Saccharomyces cerevisiae, it became obvious that d-GalUA is, to a certain degree, converted to l-galactonate (l-GalA) by an endogenous enzymatic activity. The goal of the current work was to clarify the identity of the responsible enzyme(s). A protein homology search identified three NADPH-dependent unspecific aldo-keto reductases in baker’s yeast (encoded by GCY1, YPR1 and GRE3) that show sequence similarities to known d-GalUA reductases from filamentous fungi. Characterization of the respective deletion mutants and an in vitro enzyme assay with a Gcy1 overproducing strain verified that Gcy1 is mainly responsible for the detectable reduction of d-GalUA to l-GalA.